2019
DOI: 10.1016/j.crme.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

High-order shear theory for static analysis of functionally graded plates with porosities

Abstract: The bending responses of porous functionally graded (FG) thick rectangular plates are investigated according to a high-order shear deformation theory. Both the effect of shear strain and normal deformation are included in the present theory and so it does not need any shear correction factor. The equilibrium equations according to the porous FG plates are derived. The solution to the problem is derived by using Navier's technique. Numerical results have been reported and compared with those available in the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 60 publications
0
18
0
1
Order By: Relevance
“…The normalized transverse displacement and the respective relative deviation to the reference, presented in Table 2, were obtained by Equations (21) and (22), respectively.…”
Section: Porosity Distribution Model 1 (M1)mentioning
confidence: 99%
“…The normalized transverse displacement and the respective relative deviation to the reference, presented in Table 2, were obtained by Equations (21) and (22), respectively.…”
Section: Porosity Distribution Model 1 (M1)mentioning
confidence: 99%
“…Their studies revealed a significant effect of porosity on natural frequencies, displacements, and tensions. In a recent work, S. Merdaci and H. Belghoul [27] stated the importance of taking into consideration the porosity effect when designing functionally graded components. To this purpose, they worked on the bending behavior of porous functionally graded plates, aluminum being the metal phase, and alumina the ceramic phase, concluding that the inclusion of porosity parameter increases the deflection and the transverse shear stresses, and decreases the axial stress.…”
Section: Porosities Distributionmentioning
confidence: 99%
“…Porosities created by a sequential multi-step infiltration process inside FGM specimens was studied by Merdaci [33]. The impact of porosity in the architecture of FGM structures subjected to static was analyzed by Zenkour [34], Merdaci et al [35], Wattanasakulpong et al [36], Rezaei et al [37] studied dynamic loads and reported that they should be taken into account. Consequently, more and more attention has been paid in recent years to studies dedicated to the static and dynamic behavior of FGM material structures.…”
Section: Introductionmentioning
confidence: 99%